Empowerment of Health Cadres for Sanitation and Health Promotion, Gambang Village, Jombang - Edi, Imam Sarwo; Sari, Ernita; Yaimin (Frontiers in Community Service and Empowerment, 2025)
Inadequate organic waste management in rural communities poses significant environmental and public health challenges, necessitating sustainable interventions at the grassroots level. This community service initiative aimed to establish waste management capacity in Gambang Village, Gudo District, Jombang Regency, through the implementation of Takakura composting systems toward achieving Ecovillage status. The intervention employed a mixed-method approach combining physical resource provision, educational counseling, and hands-on training. Ten Takakura composting units were distributed to health cadres, accompanied by comprehensive training sessions on composting techniques and organic waste utilization. Educational materials were delivered by faculty and students from the Environmental Health Department of the Surabaya Health Polytechnic, Ministry of Health, to health cadres and community residents. Knowledge acquisition was assessed through pre-post test measurements across multiple environmental health domains. Results demonstrated substantial improvements in participant knowledge: biopore understanding increased from 15% to 70%, infiltration well comprehension rose from 10% to 80%, and dental health awareness improved from 13% to 74%. The composting demonstration activities generated considerable enthusiasm among health cadres, evidenced by active participation in discussion forums and question-answer sessions regarding Takakura tool applications and benefits. The intervention successfully enhanced health cadres' practical skills in compost production and organic waste management. This community-based approach demonstrates promising potential for replicating sustainable waste management practices across neighboring communities, thereby advancing the broader objective of establishing Self-Reliant Waste Villages (Ecovillages) in rural Indonesia. The integration of participatory training methods with tangible resource provision proved effective in fostering community ownership and sustained behavioral change in environmental health practices.